Nanobodies against surface biomarkers enable the analysis of tumor genetic heterogeneity in uveal melanoma patient‐derived xenografts. (19th April 2017) - Crépin, Ronan; Gentien, David; Duché, Angeline; Rapinat, Audrey; Reyes, Cecile; Némati, Fariba; Massonnet, Gérald; Decaudin, Didier; Djender, Selma; Moutel, Sandrine; Desrumeaux, Klervi; Cassoux, Nathalie; et al.
Summary: Monoclonal antibodies specific for biomarkers expressed on the surface of uveal melanoma (UM) cells would simplify the immune capture and genomic characterization of heterogeneous tumor cells originated from patient‐derived xenografts (PDXs). Antibodies against four independent tumor antigens were isolated by panning a nanobody synthetic library. Such antibodies enabled flow cytometry‐based sorting of distinct cell subpopulations from UM PDXs and to analyze their genomic features. The complexity and specificity of the biochemical and genomic biomarker combinations mirrored the UM tumor polyclonality. The data showed that MUC18 is highly and universally displayed on the surface of UM cells with different genetic background and consequently represents a reliable pan‐biomarker for their identification and purification. In contrast, the other three biomarkers were detected in very variable combinations in UM PDX cells. The availability of the identified nanobodies will be instrumental in developing clone‐specific drug evaluation and rational clinical strategies based on accurate genomic profiling.